The use of a bite fork to help mobilize the maxilla after downfracture during the Le Fort I osteotomy: a technical note - Shinohara, Elio Hitoshi [UNESP]; Kaba, Shajadi Carlos Pardo; Ruiz, Marcelo Martinson; horikawa, fernando kendi (Springer Nature, 2014)
Introduction The Le Fort I osteotomy is indicated to reposition the maxilla in the surgical correction of dentofacial deformities. Although it is a known surgical step, like any surgical procedure, it can have complications and difficulties; among these, the initial mobility of the jaw is very common after completing all corticotomies. Methods The authors present a technique in which the bite fork is used as an auxiliary tool in maxilla downfracture, especially in cases of maxillary impaction where vertical space is created on the walls of the corticotomy. Findings As the bite fork acts as a scraper with a long leverage arm, an advantage would be the better distribution of forces along the corticotomy, minimizing the risk of bad fracture and facilitating maxillary downfracture movement.
Keywords: Maxillary osteotomy; Orthognathic surgery; Dentofacial; Le fort I osteotomy